Physical and Chemical Properties of Pekmez Molasses Produced with Different Grape Cultivars - Cihat Türkben; Senem Suna; Gökçen İzli; Vildan Uylaşer; Cevdet Demır (Journal of Agricultural Sciences)
In this study, some physical and chemical properties of pekmez samples produced using the traditional method with fourteen different grape cultivars were investigated. The water-soluble dry matter, pH, titratable acidity and hydroxymethylfurfural HMF content of the samples were determined to be 66.19-80.57%, 3.59-5.23, 0.27-1.81 g 100 g-1 and 5.93-762.22 mg kg-1, respectively. The mean fructose and glucose contents of the pekmez samples were determined to be 28.42 g 100 g-1 and 31.67 g 100 g-1, respectively. The densities and electrical conductivities varied between 1.33-1.43 g cm-3 and 1.96-4.51 mS cm-1, respectively. The content of the macro element K identified in the pekmez samples 4449.86 mg kg-1 was greater than that of Ca 1275.52 mg kg-1 , P 369.96 mg kg-1 , Mg 344.79 mg kg-1 and Na 119.56 mg kg-1 . The pekmez samples have antioxidant activities, ranging between 38.20 to 64.45 µmol TE g-1. Six phenolic compounds, caffeic acid, ellagic acid, ferulic acid, gallic acid, p-coumaric acid and rutin hydrate, were identified in the pekmez samples, and significant differences were observed between samples P